INOVASI PENGEMBANGAN MOTIF BATIK DIGITAL BAGI IKM BATIK SEMARANG - Wibawanto, Wandah; Nugrahani, Rahina (Indonesian Journal of Conservation, 2018)
The batik market experienced a significant increase - demanding the batik industry players to innovate. However most of the batik produced by traditional and small-scale industries (IKM batik). This study aims to encourage the productivity of IKM batik through the D'Batik software. D'Batik's software has several features to create batik motifs, which can be operated by ordinary people. The D'batik software was designed using the Software Development Life Cycle (SDLC) method with a prototyping model. The software was then tested in two locations - the village of Batik Bubakan Semarang and the batik center located in the Batik Village of Malon Gunungpati. The use of the D'Batik application can increase productivity by reducing the motifs creation time by 11.7 times faster. Future research can focus on the application of digital motifs to the technology of printed batik and stamped batik.